Stock photos of the Medford/Somerville campus, including inside Tisch Library and the Science and Technology Center. Photo 024 - Loeb, Brian (Tufts Archival Research Center, 2008)
Stock photos of the Medford/Somerville campus, including inside Tisch Library and the Science and Technology Center.